Safety and termiticidal efficacy of gliricidia sepium leaf extract: dermal irritation and toxicity againts Coptotermes curvignathus - Lalu Busyairi Muhsin; Nurul Indriani (Acta Chimica Asiana, 2026)
The overuse of synthetic insecticides in agriculture and household pest control raises concerns regarding health risks, environmental toxicity, and insect resistance. In Indonesia, about 15% of agricultural and plantation land is affected by pest infestations, with Coptotermes curvignathus recognized as one of the most destructive species due to its wood-boring activity. This study aimed to develop an eco-friendly insecticide using Gliricidia sepium leaf extract, which contains bioactive compounds such as steroids, tannins, and saponins with insecticidal potential. Four formulations were prepared with extract concentrations of 0 g (F0), 0.15 g (F1), 0.3 g (F2), and 0.45 g (F3) in 100 mL solvent. Physicochemical evaluations included pH measurement, stability observation, and homogeneity testing, while safety was assessed through dermal irritation tests on rabbits using the Draize method. Efficacy against termites was evaluated using probit analysis (IBM SPSS v22). Results showed that all formulations were physically stable, homogenous, and exhibited suitable pH values. Irritation testing revealed no erythema or edema, with primary irritation indices below 0.5, classifying the formulations as non-irritating even at low pH values. Insecticidal testing demonstrated complete termite mortality, with the F3 formulation showing the most rapid and potent effect. These findings indicate that G. sepium extract-based formulations are safe, effective, and environmentally friendly, supporting their potential as botanical insecticides to replace synthetic alternatives in sustainable pest management systems.